(untitled) (Research, Society and Development, 2021)
Epilepsy is a brain disorder characterized by a continuous predisposition to the appearance of epileptic seizures and by the neurobiological, cognitive, psychological and social consequences of this disease. The definition of epilepsy requires the presence of at least one epileptic seizure. Children with epilepsy are at higher risk for learning disabilities compared to healthy children and those with other chronic childhood diseases. A narrative review of the literature was carried out, including articles indexed in digital platforms, Literatura Latino-Americana e do Caribe em Ciencias da Saúde (LILACS), Health Information from the National Library of Medicine (Medline), Web of Science, in the electronic library Scientific Eletronic Library On-line (SciELO), and PubMed, published in the period between 2017 and 2020. Learning disorders are more frequent among children with epilepsy, with a significant predominance in males; Rolandic Epilepsy is the one with the greatest association with learning disorders; the earlier onset of seizures is related to greater cognitive impairment and there is a high comorbidity between epilepsy, Attention Deficit and Hyperactivity Disorders and generalized learning disorders.